Membangun Kemandirian Ekonomi: (Program Literasi Keuangan Untuk Masyarakat Desa Ongko) - Hambali, Denny; Muhammad Rizqi, Reza; Intan Syahfitri, Diah (Institut Agama Islam Hamzanwadi NW Pancor, 2024)
Economic independence is an important factor in improving community welfare, especially in villages that still depend on the agricultural sector and small businesses. This community service activity aims to improve financial literacy in Ongko Village, Empang District, Sumbawa Regency. Through this program, we provide training and mentoring on financial management, budget planning, and an understanding of simple investments that can be made by local communities. The methods used include lectures, interactive discussions, and hands-on practice involving participants in financial management simulations. By involving the community in every stage of the activities, this program aims to build awareness of the importance of financial literacy in making better economic decisions. The results of these activities are expected to improve the skills and knowledge of the community in managing their personal and business finances, thus encouraging economic independence. In addition, the program also aims to create a more prosperous and self-reliant community, which in turn can contribute to the overall economic development of the region. Thus, this service is the first step in building a strong economic foundation for the people of Ongko Village.